1979
DOI: 10.1515/botm.1979.22.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Production and Biomass of Cladophora prolifera (Chlorophyta, Cladophorales) in Bermuda

Abstract: A bloom of the macroalga Cladophora prolifera (Chlorophyta, Cladophorales) has recently been reported in Bermuda. The present study summarizes results of experiments conducted in June, 1977, designed to measure rates of primary production and to determine biological, physical and chemical factors controlling the rapid spread of the plant. Productivity was measured using three different methods: 14 C uptake, growth and biomass accumulation. Production values for the alga as estimated by these three methods were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
2
17
0
Order By: Relevance
“…and Gracilaria sp. (Conover 1958;Bach and Josselyn 1979;McComb et al 1979;Thorne-Miller et al 1983;Thybo-Christiansen et al 1993). This may be evidence that such ceilings as we posit do exist.…”
Section: Resultsmentioning
confidence: 99%
“…and Gracilaria sp. (Conover 1958;Bach and Josselyn 1979;McComb et al 1979;Thorne-Miller et al 1983;Thybo-Christiansen et al 1993). This may be evidence that such ceilings as we posit do exist.…”
Section: Resultsmentioning
confidence: 99%
“…Bach & Josselyn (1979) demonstrated that light limitation occurred around 10 m, thus explaining algal depth distribution. Schramm & Booth (1981) suggested that excessive growth of C. prolifera was not the result of nutrient enrichment per se but was due to its competitive advantages, namely the ability to tolerate H 2 S and anaerobic conditions.…”
Section: General Commentsmentioning
confidence: 92%
“…In the tropics, specifically on the reefs around Bermuda, C. prolifera has formed nuisance blooms for several decades, but these are generally persistent and occur in protected, shallow, nearshore environments (Bach & Josselyn 1978, 1979, Lapointe & O'Connell 1989. In southeast Florida the green alga Codium isthmocladum has been growing excessively in deep water for some time; proliferation of this species has been blamed on deep offshore sewage seeps (Lapointe 1997).…”
Section: Abstract: Algal Blooms · Cladophora Sericea · Coral Reefs ·mentioning
confidence: 99%
See 2 more Smart Citations